The Effectiveness Of Android Based Applications An Adherence Monitoring System For Adolescent Female Consumption Fe Tablets - Yuni Handayani; Sugeng Winarso; Farida Wahyu Ningtyias (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2021)
Introduction: The level of adherence of adolescent female to the consumption of Fe tablets is an indicator of the success of the program of giving Fe tablets. Objective: To analyze the effectiveness of the use of android-based applications as a monitoring system for adherence with adolescent female consuming Fe tablets . Methods: This research approach is quantitative Quasi Experimental using Pre-Post Control Group Design. This study observes or measures the independent variable and the dependent variable at the same time or at one time. The population of this study was the female youth of SMAN 5 Jember grade 3 with a total of 123 respondents. The technique of taking simple random sampling consisted of 2 groups, 39 adolescent female became the experimental group by being given an android application and 39 adolescent female became the control group. The technique of collecting data is in the form of questionnaires and observations to determine the respondent's adherence with consuming Fe tablets . Results: Data analysis used a comparison test between the control and experimental groups with a P value of 0.000 less than 0.05. There is a significant difference between the adherence of adolescent female to take Fe tablets between the experimental group and the control group. Conclusion: It can be concluded that there is an effective use of android-based applications that can increase the adherence of adolescent female in consuming Fe tablets compared to the provision of activities that have been running previously. It is hoped that there will be development on an Android-based application to add blood to be used as a monitoring system.